Renovação no espírito e serviço ao homem: uma atualização do III Documento de Malinas - Adorno, Leandro Rasera (2022)
In his first public meeting with the Catholic Charismatic Renewal on June 1st, 2014, Pope Francis would surprise charismatics by waving the unknown Malinas' Documents as a safe path for the Church's charismatic expressions from then on. Among the six documents that make up this collection, Francis would emphasize the III Document of Malinas entitled Charismatic Renewal and social action (1979), based both on its message of convergence between the charismatic and liberation dimensions that erupted within the Catholic Church since the Second Vatican Council, and the uniqueness of its authors: Cardinal Léon Joseph Suenens (1904-1996), one of the main protagonists of Vatican II and responsible for inserting the Catholic Charismatic Renewal within the Church, and Dom Helder Camara (1909-1999), one of the main organizers of the Episcopal Conferences during the Council and a symbol of the liberating Church in Latin America. Therefore, it could be said that the III Document of Malinas portrays in a significant way that integral christian outlined by the conciliar aggiornamento. Therefore, in order to provide a substantial update of this document, this research will be dedicated to discuss the ecclesiological renewal triggered by the Second Vatican Council and the roots and unfolding of the post-conciliar charismatic and liberating currents, to conclude signing how the pontificate of Pope Francis inaugurates a new phase in the process of acceptance of these currents, after decades of divergence between the ecclesial and theological movements originated from them (CCR , CEB's, TL etc.)